Advancing research on computer game consumption: A future research agenda. Issue 6 (21st October 2015) - Seo, Yuri; Buchanan‐Oliver, Margo; Fam, Kim‐Shyan
Abstract: Computer games have become an important part of consumer culture. Moreover, they drive cultural and societal advancements that serve and benefit postmodern consumers. In this introductory article to the special issue, we discuss recent developments and outline research directions that will inform future inquiries into the marketing and consumer behaviour issues associated with computer game consumption. We begin with an overview of previous research on computer games in the marketing and consumer behaviour literature. Next, we provide an integrative summary of the articles that were selected for this special issue. Finally, we draw the threads together in order to elicit opportunities for future research in the area. Copyright © 2015 John Wiley & Sons, Ltd.